Cancer Pattern among Adults in Najran, Saudi Arabia - 2014-2019 - Badheeb, Ahmed M.; Nagi, Nadeem M.; Badheeb, Mohamed A. (International Journal of Innovative Research in Medical Science, 2020)
Background: Najran is one of the thirteen regions in Saudi Arabia, located in the southwest of the country with a recently established oncology center and cancer registry. This paper describes for the first time the incidence of cancer in this region which has a unique geographic and demographic attribute. Methodology: This is a retrospective descriptive study that included all adult (diagnosis age >14 years) cancer patients captured by Najran regional cancer registry in the period of 2014 to 2019. Available data, including demographics, diagnosis, site of the tumor, and histopathology were analyzed. Pediatric malignancies were excluded. During the studied period, a regional registry was established and linked to the central Saudi Cancer Registry. All confirmed cancer cases in Najran were captured in this registry. Results: The Total number of records was 1600 diagnosed over a 6-year period (range, 200-330 per year). More females were reported (54.6%) than males (45.4%). The median age was 52 years (SD, ±19). The three most common cancers were breast (14.2 %), thyroid (11.8%), and Colorectal (8.4%). Among the females, breast (25.3%) was the most common cancer followed by thyroid (16.7%), and colorectal (7%); while in males, colorectal cancers (10.2%), hepatocellular carcinoma (6.7%), and leukemia (6.6) were the most common. Conclusions: Breast cancer in females and colorectal cancer in males were the most frequent types of solid malignancies in Najran, Saudi Arabia. Our study shows that the pattern of cancers bears some similarities with the national and Gulf data with some differences that warrant further exploration.